PERANCANGAN SISTEM INFORMASI PENGELOLAAN SALURAN AIR DI KOTA PONTIANAK BERBASIS WEB - Putri, Falentin Yusdani; Safriadi, Novi; Nasution, Helfi (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2016)
Pontianak City which lies between 0.2 to 1.2 meters above sea level making some areas very prone lower submerged in water, which often floods in certain roads, sometimes almost in all cities. One reason is that the drains are not able to drain water discharge in the rain, and seawater is being installed, or in other words there is no balance between the water flow and the capacity of existing channels. Most of the existing settlement areas that do not have a water channel so that rain water and domestic sewage flows directly into the page or to the ground. While in some settlements have provided drainage channels are not well maintained so that the experience of sedimentation. The government's efforts in managing and maintaining waterways have limited resources and personnel. The area is vast and difficult to reach areas that result in program management and maintenance of the channel not performing optimally. The lack of information led to delays in the government's performance in addressing these issues, so that people have an important role in helping the government to participate in delivering the existing problems. management information system drains very necessary because it can provide information drains well from the age of channels, detailed planning of the development and maintenance and water channel normalization, so that it can assist the government in maintaining and managing the drains in the city of Pontianak.